The interfacial stability of single crystal superalloy affected by the phase structure of the Ni-Al coating. (1st April 2023) - Wen, Jiao; Sun, Jingyong; Du, Boxuan; Chen, Yu; Yan, Xin
Abstract: Interfacial stability between the bond coating and single crystal superalloy substrate is crucial for their long-term performance at elevated temperatures. Herein, we designed coatings with various phase structures and used the typical single crystal superalloy René N5 as the substrate to investigate the intrinsic mechanism underpinning recrystallization using experiments combined with atomistic simulations. Experimentally, recrystallization occurred in the specimen with coatings of medium Al content (CA-25 specimen); in contrast, there was no secondary reaction zone in the CA-30 specimen with coatings of the highest Al content. From simulations, the nudged elastic band calculation demonstrated that a higher energy barrier (ΔE0 ) was required for new grain nucleation in the substrate under β-NiAl grains, which existed in the CA-30 coating. Our findings provide a fundamental understanding of interfacial stability and benefit the design of bond coatings for superalloys. Graphical abstract: Image, graphical abstract